The risk of 'tik' and the crime rate - Berg, Julie (2016)
This article provides an overview of the annual crime statistics as released by the South Africa Police Service (SAPS) from 1994 to 2005, which will be portrayed in graphics and briefly discussed. But, as the crime rates will demonstrate, there is need for a closer look at and interpretation of South Africa’s drug-related crime. Hence the focus of this article will be on the drug-crime nexus, more specifically on the drug, methamphetamine, known colloquially as ‘tik’